The Application of Dynamic Compaction to HFO Tanks - Hamidi, Babak; Varaksin, S.; Nikraz, Hamid (Australian Geomechanics Society, 2011)
Three heavy fuel oil (HFO) tanks with diameters of up to 60 m, a pump station, a pump shed station and a vent stack station have recently been constructed as part of the HFO Tank Farm in Ras Laffan, Qatar. The project was located in an area near the sea with high groundwater level. The ground was composed of 11 to 12 m of silty sand and gravel with cobbles and boulders with diameters up to 300mm followed by limestone. The preliminary soil investigation using Standard Penetration Test (SPT) indicated that while the soil was generally dense, but a loose layer of sand was identified and soil improvement was stipulated. During later stages, a supplementary geotechnical investigation using the Menard Pressuremeter Test (PMT) indicated that the high SPT blow counts were not representative of the actual ground conditions and that due to the presence of the large cobbles the soil had erroneously been represented as dense. In fact, the soil was loose from the surface down to bedrock. Dynamic Compaction was used to improve the soil's strength and to reduce its compressibility. PMT in conjunction with finite element analysis were used to verify the ground condition after ground treatment.